Ammonia Fiber Expansion (AFEX) as spin off technology from 2nd generation biofuel for upgrading cereal straws and stovers for livestock feed - Blümmel, Michael; Teymouri, F.; Moore, J.; Nielson, C.; Kodukula, P.; Pothu, S.; Devulapalli, R. (Elsevier, 2018)
Ten cereal straws and stovers from India were treated using the ammonia fiber expansion (AFEX) technique to explore the effectiveness of the AFEX technique for releasing sugars from structural carbohydrates and for the upgrading of cereal crop residues as livestock feed. Recovery of glucose and xylose in AFEX treated material was about three times the recovery in untreated material. AFEX treatment increased recovery of glucose between 60 and 85% and of xylose between 50 and 85% of their theoretical yields. AFEX treatment increased average crude protein (CP) by 260% (CP content: 62 vs 161 g/kg). Cell wall content as estimated by NDF decreased on average by 47 g/kg (NDF: 656 vs 609 g/kg) while cellulose contents estimated as ADF apparently increased by 23 g/kg (ADF: 443 vs 466 g/kg). Lignin contents estimated as ADL did not significantly differ between untreated and treated material. Measured after 24 h of incubation, AFEX treatment consistently and significantly increased in vitro gas production (42.9 vs33.3 ml/200 mg), in vitro apparent digestibility (493 vs 630 g/kg) and true digestibility (624 vs 755 g/kg) and in vitro metabolizable energy content (6.9 vs 8.6 MJ/kg). Treatment changes in digestibility estimated based on in vitro gas production generally agreed with gravimetric estimates based on undigested residues, making it unlikely that the effect of AFEX treatment on digestibility was overestimated by unrecovered soluble but un-fermentable substrate. Increases in CP content and in vitro digestibilities upon AFEX treatment were unrelated to CP content and in vitro organic matter digestibilities (IVOMD) of untreated base material, though increases in IVOMD upon treatment tended (P = 0.07) to be lower in material with high (>530 g/kg) baseline IVOMD.